Dissemination of Linezolid Resistance Through Sex Pheromone Plasmid Transfer in Enterococcus faecalis - Zou, Jiaqi; Tang, Zhaobing; Yan, Jia; Liu, Hang; Chen, Yingzhu; Zhang, Dawei; Zhao, Jinxin; Tang, Yu; Zhang, Jing; Xia, Yun (Frontiers in Microbiology, 2020)
Despite recent recognition of the ATP-binding cassette protein OptrA as an important mediator of linezolid resistance in Enterococcus faecalis worldwide, the mechanisms of optrA gene acquisition and transfer remain poorly understood. In this study, we performed comprehensive molecular and phenotypic profiling of 44 optrA-carrying E. faecalis clinical isolates with linezolid resistance. Pulse-field gel electrophoresis and DNA hybridization revealed the presence of optrA in the plasmid in 26 (59%) isolates and in the chromosome in 18 (41%) isolates. Conjugation experiments showed a successful transfer of optrA in 88.5% (23/26) of isolates carrying optrA in plasmids while no transfer occurred in any isolates carrying optrA in the chromosome (0/18). All 23 transconjugants exhibited in vitro resistance to linezolid and several other antibiotics and were confirmed to contain optrA and other resistance genes. Plasmid typing demonstrated a predominance (18/23,78%) of rep9–type plasmids (pCF10 prototype) known to be the best studied sex pheromone responsive plasmids. Full plasmid genome sequencing of one isolate revealed the presence of drug resistance genes (optrA and fexA) and multiple sex pheromone response genes in the same plasmid, which represents the first sex pheromone responsive plasmid carrying optrA from a clinical isolate. PCR-based genotyping revealed the presence of three key sex pheromone response genes (prgA, prgB and prgC) in 23 optrA-carrying isolates. Finally, functional studies of these isolates by clumping induction assay detected different degrees of clumping in 17 isolates. Our analysis suggests that optrA-mediated linezolid resistance can be widely disseminated through sex pheromone plasmid transfer.